Germination and recruitment of clusia spp. (linneo) in a tropical fragmented and very humid colombian forest - Pulido Blanco, Victor Camilo; Burgos Ayala, Aracely (M+A. Revista Electrónica de Medioambiente, 2016)
Tropical forest fragmentation increases the size of the edges and make micro environmental gradients between zones of the same fragment (border and interior), altering biotic and abiotic interactions necessary for the establishment of plants. After fragmentation processes, the juvenile stages of plants, such as germination and recruitment are the most vulnerable and crucial for the establishment of populations. In this study, the incidence of the edges and the inside was evaluated in a fragment of tropical forest on the germination and recruitment of Clusia spp. naturally present along eight transects on the interior and edge of a fragment. higher germination and recruitment was found on the edge than on the inside of the fragment. The results are mainly attributed to increased availability of light at the edge due to loss of canopy density over the death of trees by wind buffeting, and a higher concentration of nutrients too, as it is a buffer zone. However, variables act jointly and simultaneously complicating the individual analysis is done on them.
Keywords: Edge; biotic interactions; interior; fragmentation.